Measuring Levels of IL4, TNF Alpha and Cortisol among Diabteic Type 2 Individual in Samarra City - AL-Elyan, Umer Abdullah Ahmed (American Journal of Biology and Natural Sciences, 2025)
The current study involved sample collection from February 10, 2023, to June 5, 2023. Fifty samples, including 30 diabetic patients and 20 healthy controls, were collected from Samarra General Hospital and its clinics. Serum levels of tumor necrosis factor alpha (TNF-α), interleukin-4 (IL-4), and ketones were measured using a radioactive enzyme assay technique. The study results showed a significant increase in tumor necrosis factor alpha (TNF-α) levels by 273.0 ± 24.04 pg/ml in the patient group compared to the control group (58.5 ± 13.18 pg/ml), in addition to higher cortisol levels in the patient group (0.07 ± 3.94 pg/ml) compared to the control group (0.05 ± 1.53), while the results showed increase in interleukin-4 levels in the patient group (0.37 ± 0.158) compared to the control group (0.58 ± 0.107). We conclude from these results that elevated levels of inflammatory factors play an important role in detecting the development of type 2 diabetes in patients.